2022
DOI: 10.1042/bst20220591
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into protein folding by the eukaryotic chaperonin complex CCT

Abstract: The cytosolic chaperonin CCT is indispensable to eukaryotic life, folding the cytoskeletal proteins actin and tubulin along with an estimated 10% of the remaining proteome. However, it also participates in human diseases such as cancer and viral infections, rendering it valuable as a potential therapeutic target. CCT consists of two stacked rings, each comprised of eight homologous but distinct subunits, that assists the folding of a remarkable substrate clientele that exhibits both broad diversity and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Our results showed that the function of CCT Complex is regulated by germ cell-specific STYXL1 and is essential for sperm flagella development. In eukaryotic life, the chaperonin CCT Complex is indispensable for folding the cytoskeletal proteins actin and tubulin along with an estimated 10% of the remaining proteome 61 . Although CCT complex has a certain structure with eight subunits, it is obvious that the functions of the CCT complex are varied and related with lots of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the function of CCT Complex is regulated by germ cell-specific STYXL1 and is essential for sperm flagella development. In eukaryotic life, the chaperonin CCT Complex is indispensable for folding the cytoskeletal proteins actin and tubulin along with an estimated 10% of the remaining proteome 61 . Although CCT complex has a certain structure with eight subunits, it is obvious that the functions of the CCT complex are varied and related with lots of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A tailless complex polypeptide 1 ring complex (TRiC), also known as chaperonin containing tailless complex polypeptide 1 (CCT), is a prominent eukaryotic cytoplasmic chaperonin that has several essential cellular functions [ 201 , 202 , 203 ]. TRiC/CCT consists of two oligomeric rings, each composed of eight homologous subunits, termed CCT1-5 in lower eukaryotes and CCTα-θ in mammals [ 201 , 202 , 203 ]. These oligomeric rings associate with each other, forming a central cavity, which serves as a place for protein client folding [ 204 , 205 ].…”
Section: Tric/cct Chaperoninsmentioning
confidence: 99%
“…CCT complex is a conserved multi-subunit complex consisting of two back-to-back rings, each containing eight related but distinct paralogous subunits (named CCT1 to CCT8), forming a complex of approximately 1000 kDa. Eukaryotic CCT complex mediates nascent client peptides folding by encapsulating them in its enclosed central cavity [ 51 , 52 , 53 , 54 , 55 ]. Actin and tubulin captured by PFDc absolutely require CCT for refolding so the cytoskeleton is much more dependent on this biomacromolecules.…”
Section: Dynamic Functions Of Prefoldin Proteins In Plantsmentioning
confidence: 99%
“…Actin and tubulin captured by PFDc absolutely require CCT for refolding so the cytoskeleton is much more dependent on this biomacromolecules. In human, dysfunction of the CCT chaperonin leads to severe disease symptoms such as neurological-related disorders and cancer, largely due to their dysregulation in protein proteostasis and aggregation [ 51 , 54 , 55 , 56 , 57 ]. With similar construction and function, the Arabidopsis CCT complex is also assembled from eight CCT subunits, except that CCT6 has two coding regions that are 96% identical [ 12 , 58 ].…”
Section: Dynamic Functions Of Prefoldin Proteins In Plantsmentioning
confidence: 99%